The Right of Workers with Disabilities: Legal Instrument and Challenges in Indonesia - Muh. Arief Syahroni; Abdullah Fikri; Eka Nanda Ravizki (UNES Law Review, 2024)
Nowadays, people with disabilities still experience various acts of discrimination. For example, mainly constrained by the requirements of "no physically disabled" which has always been one common absolute requirement for every person when registering for certain jobs. Therefore, states should expressly provide legal protection to people with disabilities and provide opportunities for people with disabilities to be able to work like normal people in general and not consider their limitations as something that could hamper their work. Two important and interesting points will be discussed in this paper. First, people with disabilities are discriminated Often against while facing job recruitment, especially for Indonesian Attorney Civil Servants. Second, it is important to know the responsibility of the state in protecting people with disabilities. The type of research used in the present research is doctrinal-comparative legal research. This present research conducts library research to obtain secondary sources of law (authorities). This paper found that various legal instruments on disability rights that there is no correlation with each other, so it does not create an integrated system to protect the rights of disabilities in obtaining jobs. Although there has been affirmative action in the recruitment process prosecutor (civil servant), it is not enough to give the disabilities an equal opportunity to participate in the recruitment process